UTILIZING ELT PODCASTS TO DEVELOP LISTENING COMPREHENSION - Rekha Asmara (Universitas Islam Ogan Komering Ilir Kayuagung, 2017)
The development of listening comprehension tends to be ignored in the process of teaching and learning English as a foreign language. English language teachers often use the same listening materials for much of the time of their teaching. A new trend for teaching listening comprehension known as ‘ELT podcast' is thus recommended and explained in this article. Educators saw the beneficial backwash of ELT podcasts for English teaching and learning especially in the teaching of listening comprehension. It offers students extra listening practice both inside and outside of English classes. The aim of this study was to help both teachers and students in overcoming the ignorance of listening comprehension development and in providing interesting, fun, and accessible teaching materials for listening comprehension